2021
DOI: 10.3390/cancers13194790
|View full text |Cite
|
Sign up to set email alerts
|

Pertuzumab and Trastuzumab Combination with Concomitant Locoregional Radiotherapy for the Treatment of Breast Cancers with HER2 Receptor Overexpression

Abstract: Background: The combination of pertuzumab and trastuzumab dual HER2 blockade with concomitant curative dose locoregional breast radiotherapy in patients with metastatic breast cancer is an important part of treatment strategy. Methods: This was a retrospective study conducted at the Institut Curie on all patients treated concomitantly with pertuzumab/trastuzumab and locoregional breast radiotherapy. Toxicity was evaluated according to the NCICTCAEv4.0. Overall survival, progression-free survival and locoregion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Indeed, it is known that independently, HER2 blockade on the one hand [ 26 ] and locoregional RT for BC [ 27 ], especially in case of breast node irradiation, on the other hand, could induce cardiac toxicity. Several retrospective and prospective studies have evaluated the skin and cardiac toxicity of this combination ( Table 1 [ 28 , 29 , 30 , 31 , 32 ]). The ranges of ≥ Grade 2 cardiac, skin, and esophagitis toxicity were 0–25.8%, 2.9–30.9%, and 1.6–12%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it is known that independently, HER2 blockade on the one hand [ 26 ] and locoregional RT for BC [ 27 ], especially in case of breast node irradiation, on the other hand, could induce cardiac toxicity. Several retrospective and prospective studies have evaluated the skin and cardiac toxicity of this combination ( Table 1 [ 28 , 29 , 30 , 31 , 32 ]). The ranges of ≥ Grade 2 cardiac, skin, and esophagitis toxicity were 0–25.8%, 2.9–30.9%, and 1.6–12%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Several more recent retrospective studies reported the good safety of the combination of RT and dual HER2 receptor inhibitor [ 33 , 34 ]. In particular, Aboudaram et al have recently shown that the administration of dual HER2 blockade in 55 patients receiving locoregional RT was safe in terms of skin, gastrointestinal, and general toxicity [ 31 ]. No significant cardiac toxicity was observed, apart from a slight decrease in left ventricular ejection fraction (LVEF), which is expected during the HER2 blockade [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…More recently, in a large retrospective cohort of 55 patients, the combination of locoregional breast RT with PT resulted as well tolerated. Particularly, only three cases of grade 3 skin toxicity were reported, suggesting a good safety profile for the association [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pertuzumab, a HER dimerization inhibitor, is the first humanized monoclonal antibody in a new class of drugs and is approved for use in combination with trastuzumab as therapy in HER2-positive patients [ 7 ]. Pertuzumab (Perjeta ® ) was approved for marketing in the United States (US), the European Union (EU), and China (CN) in 2012, 2015, and 2018, respectively [ 7 , 8 ]. Since pertuzumab binds to a different epitope than trastuzumab, combination therapy with pertuzumab and trastuzumab results in a more complete blockade of HER2 signalling than trastuzumab monotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Since pertuzumab binds to a different epitope than trastuzumab, combination therapy with pertuzumab and trastuzumab results in a more complete blockade of HER2 signalling than trastuzumab monotherapy. Clinical studies have shown that the combination of these two HER2 inhibitors has a good synergistic effect that significantly improves clinical efficacy and prognosis [ 8 ].…”
Section: Introductionmentioning
confidence: 99%